2020
DOI: 10.1177/1354816620901953
|View full text |Cite
|
Sign up to set email alerts
|

Short-term hotel room price effects of sporting events

Abstract: A difference-in-differences analysis is used to investigate the short-term price effects of eight sporting events in Finnish Lapland. Data consist of 220,000 room bookings from the reservation system of a nine-hotels chain. Treated hotels are those located within an area where sporting events are regularly held. The control group consists of hotels further away that are not affected by the event. Robust regressions show that hotel room prices rise by 14% on average during the event, when booking and guest spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…But, the other events had no discernible effect. Falk and Vieru (2021) also discovered that there was a large variation across different sport events regarding their influence on hotel room rates. Herrmann and Herrmann (2014) pointed out that the room rate differences probably were because of the hotel star classification and the proximity to the event venue.…”
Section: Literature Reviewmentioning
confidence: 98%
See 2 more Smart Citations
“…But, the other events had no discernible effect. Falk and Vieru (2021) also discovered that there was a large variation across different sport events regarding their influence on hotel room rates. Herrmann and Herrmann (2014) pointed out that the room rate differences probably were because of the hotel star classification and the proximity to the event venue.…”
Section: Literature Reviewmentioning
confidence: 98%
“…For example, Barreda et al (2017) found that all hosting cities in Brazil for 2014 FIFA World Cup experienced an increase in hotel room rates during the event. Falk and Vieru (2021) further discovered that hotel room rates rose on average of 14% during an event. No significant positive effect of the event was identified on the hotel rates during the pre-event period, and a significant negative effect of 6% was found after the event.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Stephenson, 2018). The effects after the event are small and sometimes negative (as after winter games in Lapland: Falk and Vieru, 2020). Chikish et al (2019) use NHL and NBA unexpected lockouts as natural experiments to study the effect of sports matches on hotel occupancy around a large sports arena in L.A. Their results indicate that these stoppages had if anything a positive effect on the hotels in the area.…”
Section: Related Literaturementioning
confidence: 99%
“…the study of hotels in Charlotte, NC: Depken & Stephenson, 2018). The effects after the event are small and sometimes negative (as after winter games in Lapland: Falk & Vieru, 2020). Chikish et al (2019) use NHL and NBA unexpected lockouts as natural experiments to study the effect of sports matches on hotel occupancy around a large sports arena in L.A. Their results indicate that these Residualized arrivals in January-June on routes across cities taking part to the Champions' League group phase in the following September-December (1998-2010.…”
Section: Related Literaturementioning
confidence: 99%